From SMEs to unicorns: What role for trade, standards and new tech? - Lucian Cernat (European Centre for International Political Economy (ECIPE), 2021)
The global economy has been shaped by important, disruptive technological changes in recent years. Many of these technologies have been instrumental in our global COVID-19 response and will become the new normal. Some of these technologies have been introduced by small firms, which grew spectacularly to become 'unicorns', with very high market value and global reach, setting new technological standards in their sectors. The future competitiveness of the EU economy depends on the interplay between firm size, technological progress and ability to use the opportunities offered by global markets. This paper looks at the role of trade policy in influencing this complex interplay and offers a few tentative conclusions and recommendations.
Keywords: 330